Pengaruh Jumlah Uang Beredar dan Kurs terhadap Harga Beras di Indonesia dengan Inflasi sebagai Variabel Intervening - Anam, Muhammad Syariful; Nadila, Dian Luthvita; Iskandar, Iskandar (Jurnal Samudra Ekonomi dan Bisnis, 2021)
The study aims to determine the effect of the money supply and exchange rates on rice prices with inflation as an intervening variable. Secondary data is time series 2015-2019 from BPS and BI, and is analyzed using a path analysis model which is an extension of multiple linear regression. The results showed that the money supply had a negative and significant effect on inflation, while the exchange rate had a positive and insignificant effect on inflation. Another finding is that the money supply has a positive and significant effect on rice prices, the exchange rate has a negative and insignificant effect on rice prices, and inflation has a negative and significant effect on rice prices. The third finding is that inflation as an intervening variable only mediates the money supply to the price of rice.